A systematic review and meta‐analysis of telephone vs in‐person genetic counseling in BRCA1/BRCA2 genetic testing. Issue 2 (1st November 2020) - Bracke, Xavier; Roberts, Jonathan; McVeigh, Terri P.
Abstract: Pathogenic variants in the BRCA1 and BRCA2 genes increase the risk of breast and ovarian cancer. Individuals with identified pathogenic variants in the BRCA1 or BRCA2 gene can benefit from cancer risk‐reducing strategies. In the recent years, there has been an increase in the demand of genetic services. In light of the ongoing COVID19 pandemic, alternatives to face‐to‐face consultations have had to be considered and adopted, including telemedicine. Informed consent is necessary for genetic testing. Studies have suggested that increased levels of cancer‐specific distress may impair the patient's ability to retain information, therefore, providing informed consent. This systematic review and meta‐analysis aimed to answer if telephone genetic counseling for BRCA1 and BRCA2 genetic testing is non‐inferior to in‐person genetic counseling for the outcomes of cancer‐specific distress and genetic knowledge. Databases of Medline, Embase, PsycINFO, CINAHL, SciELO, Web of Science, CENTRAL, ProQuest Dissertation & Theses Database, Clinicaltrials.gov, EU clinical trials register were accessed to identify any published or unpublished relevant literature. Random‐effects models were used for the meta‐analysis. Four studies were included in the qualitative synthesis of the results. Three studies were included in the quantitative synthesis of the results. Telephone genetic counseling was non‐inferior compared to in‐person genetic counseling for the outcomes of cancer‐specific distress and genetic knowledge. Sensitivity analysis corroborated the main results. Telephone genetic counseling for BRCA1/BRCA2 genetic testing may be an alternative model of delivering genetic services in front of the increased demand/or when required by social context. However, the paucity of the evidence prevents from drawing strong conclusions regarding the generalizability of these results. Further research is needed to strengthen the conclusions.